Sexual Harassment in Educational Institutions in Delhi’ N.C.R. (India): Level of Awareness, Perception and Experience - Aina-Pelemo, Adetutu (Sexuality and Culture, 2017)
This study examined the level of awareness of sexual harassment in educational institutions in Delhi NCR (India). This paper grouped the results of all respondents into two categories, i.e. Private and State institutions, wherein a total number of 430 respondents were selected from ten private and state universities by simple random sampling from their respective law faculties. The statistical tools used in analyzing the data collected were frequency and chi square which revealed that the level of awareness of private or individually owned institutions is relatively high but lacks clarity, and boils down to a lower level of awareness as compared with state or government owned institutions. The findings also revealed that private universities experience sexual harassment just like state universities. Based on these results, the author recommends the augmentation of awareness programs in all universities, especially private ones. Compulsory sexual education courses for new intakes could be arranged, and final year students could also be re-oriented before they graduate.
Keywords: Awareness; Higher Educational Institutions; Internal Complaint Committee; Private and State universities; Sexual harassment